Digital literacy training to promote diffusion of digital agricultural tools to smallholder farmers - Abdelaziz, Fatma; Abay, Kibrom A. (International Food Policy Research Institute, 2024)
Digital innovations hold significant potential to address multiple forms of market failures. However, their adoption remains low and heterogenous across Africa. Smallholder farmers face significant barriers in accessing essential information, limiting their ability to seize market opportunities and enhance profitability. While numerous digital tools have been developed for farmers in the region, most are still in pilot phases. The landscape of digital agricultural innovations in Egypt, the focus of this study, presents a similar outlook, whereby the Egyptian market has an array of innovative digital study, presents a similar outlook, whereby the Egyptian market has an array of innovative digital agricultural tools that offer different services to farmers (including digital advisory agricultural and market services). Several demand and supply-side factors contribute to the low adoption of these digital innovations and their disparities among smallholder farmers in Africa and Egypt. On the supply side, the most important challenges include inadequate public and private investment in complementary infra-structure, unsustainable business models, and a misalignment in the pace of innovation. The most important demand-side challenges include lack of digital literacy, insufficient context-specific needs assessments, digital divide, and accessibility, usability, and user trust. User confidence and trust in digital tools is another important but understudied topic.. However, we lack empirically grounded evidence on alternative supply and demand-side interventions to enhance the adoption and scaling of digital innovations in various contexts, including Egypt.